THE USE OF REALIA TO IMPROVE THE SUDENTS’ SPEAKING ABILITY AT THE ELEVENTH GRADE STUDENTS OF SMU NEGERI 1 BAJENG, GOWA - Setiadi, Muhammad Astrianto; Firman, Firman (JOURNAL OF ADVANCED ENGLISH STUDIES, 2018)
The objectives of this research were to find out whether or not the use of Realia improves students’ speaking ability at the eleventh grade of SMU Negeri 1 Bajeng Kab. Gowa. The subjects of this research were the eleventh grade of students SMU Negeri 1 Bajeng Kab. Gowa in the Academic Year of 2017/2018. The number of the subjects was 30 students. This research was a classroom action research. The process of this research was conducted in three stages, including D-Test, cycle I, and cycle II. The data were collected by using observation guide in order to know the events in the classroom during teaching learning process. Besides that, the researcher also used test to get the students’ score, in order to know the improvement of students’ ability in speaking. The data were analyzed by using quantitative analysis. In this research, the researcher used Realia as a medium in teaching. The result of research shows that the use of Realia in teaching speaking can improve students’ speaking ability. It can be seen from the result of students’ average score and responses of the students. The result after getting all of the treatment using Realia, the students’ average score increased in line with the increase of the students’ achievement in each cycle. Before getting the treatment students’ average score was 3.67, and after giving treatment was 7.82, so it increased 4.15 the average score of students in the D-Test was 3.67, first cycle was 5.64, and the second cycle was 7.82. It can be concluded that by using Realia in teaching speaking, teacher can improve students’ ability in speaking